Advances in water splitting and lithium-ion batteries: pioneering sustainable energy storage and conversion technologies - Syeda Maria Hashmi; Shah Noor; Warda Parveen (Frontiers in Energy Research)
The global energy landscape is currently facing an unprecedented crisis. To address these difficulties, it is vital to create efficient and reliable energy storage and converting technologies. This review discusses the two important technologies; Water Splitting and Li-ion batteries for energy storage. Lithium-ion battery revolutionised convenient devices and electric motors with their higher energy-density, prolonged efficiency, and decreasing costs. Concurrently, Water splitting offers a pathway for hydrogen generation a clean fuel with high energy density, through electrolysis process. In this analysis, we will explore at the most recent breakthroughs, as well as the latest materials and catalysts, boosting the productivity and economic viability of water splitting. Electrode materials, electrolytes, and battery architectures that enhance performance and safety for Li-ion batteries are discussed. The integration of these technologies within renewable energy systems, highlighting their complementary roles in achieving carbon neutrality are also addressed in this review. We underscore the critical importance of water splitting and lithium-ion batteries in the sustainable energy landscape, through a comprehensive analysis of current research and future directions.